ENVIRONMENTAL CONDITIONS AS A PROVOCATIVE BACKGROUND FOR REPRODUCTION INDICES IN SABLES (MARTES ZIBELLINA) DIFFERING IN COAT PIGMENTATION HEAVINESS - S. V. Beketov; T. I. Kazakova; I. E. Chernova (Вавиловский журнал генетики и селекции)
This work concerns sable domestication at Russian fur farms. There are two ecotypes of sables: (1) dark with small body size and poorly fertile and (2) diluted with large body size and more fertile. The former lives in Siberian pine forests with a stable food potential, and the latter prefers larch forests and margins of the range.